In Vitro and In Silico Strategies for the Assessment of Fungicidal Compounds from the Bark of Bauhinia racemosa Against Dermatitis: Clinical Isolates - K. Kalaimathi; J. Maria Jancy Rani; P. Manogar; S. Vijayakumar; N. Prakash; K. Karthikeyan; G. Thiyagarajan; K. Bhavani; S. Prabhu (Mary Ann Liebert, 2022)
Objectives: Skin performs specific functions in the human body, particularly in the prevention of skin infections. Skin diseases are the fourth most common disease worldwide. Materials and Methods: The dead keratin tissue was collected from people with skin diseases in order to identify new drug candidates from traditional plants through antimicrobial exploration with B. racemosa bark extracts. The sample taken contained eight strains of fungi, which were then treated with the plant extracts. At present, the computational research was used to identify the fungicidal compound from this plant. Results: The methanol extracts show robust inhibition zones for A. niger, A. fumigatus, M. gypseum, B. dermatitis and it also reveals significant inhibition zones for C. albicans and C. berthlotiae. Among the extracts tested, extracts formulated with methanol suppressed the growth of the pathogens tested at doses of 25, 50, 75, and 100??L. For the first time, the bark extracts of B. racemosa were tested against the causative agents of skin diseases. Conclusion: According to the present docking analysis, racemosol and pacharin represent to have the highest drug potential against tested microbial proteins. This study therefore suggests that the phytocomponents such as pacharin and racemosol may act as antibiotics in suppressing microbial growth, particularly A. fumigatus and C. albicans. According to in-silico research, we conclude that due to the existence of these metabolites, racemosol may have been exposed to antifungal effects, as these molecules can either suppress microbial growth directly or have a synergistic effect with other phyto components. Ultimately, this research would be a guide for future researchers to understand the potential of this plant and its phytochemicals.